Tissue Levels of Flurbiprofen in the Rat Plantar Heel after Short-Duration Topical Iontophoresis Are Sufficient to Induce Pharmacodynamic Responses to Local Pain Stimuli - Yilu Cai; Ye Zhou; Peiyan Zhang; Yogeshvar N. Kalia; Tais Gratieri; Yong Chen (Pharmaceutics, 2020)
The objective of this study was to investigate the topical iontophoresis of flurbiprofen (FBF) as a means to enhance its local bioavailability and thereby provide an improved and targeted treatment of plantar heel pain. Initial in vitro experiments using porcine ear skin investigated iontophoretic transport of FBF under different conditions. Local FBF biodistribution in the rat paw in vivo was compared after topical or oral administration. Efficacy of pain management was investigated using a plantar incisional model by evaluating pharmacodynamic responses to local pain stimuli. The results demonstrated that iontophoresis of FBF significantly increased cutaneous deposition and transdermal permeation of FBF as compared to passive delivery—it also enabled drug input to be controlled by modulation of current density and drug concentration (r2 > 0.99). Topical iontophoresis of FBF in vivo enabled higher drug levels in skin and muscle in rat plantar aspect and superior pharmacodynamic responses to local pain stimuli, in comparison to oral and passive delivery. In conclusion, short-duration topical iontophoresis of FBF may better help to relieve plantar heel pain than oral or passive administration, which should be of clinical interest.